2002
DOI: 10.1149/1.1419705
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Copper Interconnection Layers Deposited by Electroplating Using a Copper Hexafluorosilicate Electrolytic Solution

Abstract: This paper describes the deposition and properties of copper layers electroplated from a newly developed copperhexafluoro-silicate electrolytic solution. A low stress copper layer can be obtained using this electroplating technique, with a stress ratio as defined by ⌬d/d, as low as 0.0156 in the as-deposited layers. This ratio decreases to 0.0027 and a stress-free layer is formed after annealing at 300°C. This ratio, however, is held at the higher level of 0.019 in layers deposited from the conventional copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…1. 7,8 Since the agglomeration occurred throughout the whole thickness of seed layer A, a rough surface and a stress-free ͑or low stress͒ copper seed layer was formed with this annealing. However, agglomeration only occurred at the interface with the Ta barrier layer in the thick seed layer B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. 7,8 Since the agglomeration occurred throughout the whole thickness of seed layer A, a rough surface and a stress-free ͑or low stress͒ copper seed layer was formed with this annealing. However, agglomeration only occurred at the interface with the Ta barrier layer in the thick seed layer B.…”
Section: Resultsmentioning
confidence: 99%
“…The layer stress in the electroplated copper layer ͑as-deposited͒ was observed by the shift angle of the Cu͑111͒ spectra in XRD measurements. The layer stress is proportional to the shift angle given by ⌬2, 8 and was 26 MPa in the layer deposited on the rough surfaced seed layer A, in which stress free seed layer was formed by the agglomeration. However, a higher stress ͑33 MPa͒ was applied in the layer on smooth surface seed layer B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-thick Cu deposits were used in this study: 30 μm versus 0.3 μm in [21]; -substrate influence: randomly oriented copper foil was used in this study, whereas a Ta/TaN barrier layer has been used in [22]; -the impact of the substrate on the lattice of the deposit and structure in 30 μm thick Cu is negligible, as electrodeposition was carried out under non-equilibrium conditions (overpotential). If thin films are deposited (below 1-2 μm) the impact of a substrate on crystal lattice is highly important [35,38].…”
Section: Grain Sizementioning
confidence: 99%
“…Interest in hexafluorosilicate-based electrolytes for copper electrodeposition was raised again by Hara et al [21,22]. It was shown that electroplated copper layers deposited using these baths have lower electrical resistivity, lower intrinsic stresses and larger grain size, when compared to copper layers deposited from the conventional sulphate electrolyte, even after annealing, which refines grain structure and enhances films conductivity [22].…”
Section: Introductionmentioning
confidence: 99%